DISPARITAS PEMBANGUNAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (STUDI KASUS DI DAERAH SUMBAGSEL) - Soebagiyo, Daryono (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2000)
This is well illustrated by recent research into inter-regional development growth disparities. Some researchers have followed the Neoclassical route, emphasizing the role of the Williamson Index, and then can be expressed relationship in general form that in regression and correlation coefficient analysis involving time series data. The objectives of this research was to preview the classification development of disparities and influence factors in the late five years during 1992-1996, case study in SUMBAGSEL. The Analysis can be calculated to measure the government revenue, income regional and contributed tax sectors.